A bibliometric study of global trends in diabetes and gut flora research from 2011 to 2021 - Zhang, Lu; Zhang, Hongcai; Xie, Quan; Xiong, Shuai; Jin, Fengchen; Zhou, Fan; Zhou, Hongjun; Guo, Jinhong; Wen, Chuanbiao; Huang, Biao; Yang, Fei; Dong, Yuanwei; et al. (Frontiers in Endocrinology, 2022)
Background and Objectives： Diabetes mellitus is a serious metabolic disease that causes a serious economic burden worldwide. Gut flora is a major component of diabetes research, and the aim of this study was to understand the trends and major components of research related to diabetes and gut flora in the last 11 years. Methods： We searched the Web of Science Core Collection database for articles on diabetes and gut flora related research from 2011-2021 on July 2, 2022. The literature data were analyzed for country, institution, author, steward, journal, and highly cited literature using Citespace.5.8.R3 and Vosviewer1.6.17. Results： Finally 4834 articles that met the requirements were included. The overall trend of articles published in the last 11 years is increasing, and the trend of articles published after 2019 is increasing significantly. In total, 109 countries, 4820 institutions, and 23365 authors were involved in the field of research. The highest number of publications was 1262 articles from the United States, the institution with the most publications was the University of Copenhagen with 134 articles, and the author with the most publications was PATRICE D CANI with 52 articles. Conclusion： The number of studies related to diabetes and intestinal flora is increasing and more and more researchers are involved in this field. Intestinal flora provides a key research direction for the treatment of diabetes. In the future, gut flora will remain the focus of the diabetes field.